The Participation of Interleukin Family 1 in the Development of the Inflammatory Response in Infectious Process. Part 3. Role of IL-1F4 (IL-18) - A.Ye. Abaturov; A.P. Volosovets; Ye.I. Yulish (Zaslavsky O.Yu., 2014)
The review presents the characteristics of IL-1F4 (IL-18), its mechanisms of action and value in the development of inflammatory response.